2015
DOI: 10.1139/cjc-2015-0208
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical examination of competitive β-radical-induced cleavages of N–Cα and Cα–C bonds of peptides

Abstract: Selective cleavages of N-C ␣ and C ␣ -C bonds of ␤-radical tautomers of amino acid residues in radical peptides have been examined theoretically by means of the density functional theory at the M06-2X/6-311++G(d,p) level. The majority of the bond cleavages are homolytic via ␤-scission. Their energy barriers depend largely on the ability of the radical being stabilized in the transition structures and the availability of a mobile proton in the vicinity of the ␤-radical center. The N-C ␣ bond is less favorably c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…An another high-lying structure is the b-radical FY b GG-1 (41 kJ mol À1 ), 52 in which a proton from the b-carbon of Tyr has been transferred to the N-terminal amide oxygen and the delocalization of the unpaired electron of the phenol side chain is extended to its b-carbon. Transferring the proton of the a-carbon of the N-terminal Phe to its amide oxygen can give F a YGG-1, known as the a-radical with the spin density delocalized among the N-terminal NH 2 , the a-carbon of Phe and the N-terminal amide group.…”
Section: Theoretical Geometries and Irmpd Study Of [Fygg] +mentioning
confidence: 99%
“…An another high-lying structure is the b-radical FY b GG-1 (41 kJ mol À1 ), 52 in which a proton from the b-carbon of Tyr has been transferred to the N-terminal amide oxygen and the delocalization of the unpaired electron of the phenol side chain is extended to its b-carbon. Transferring the proton of the a-carbon of the N-terminal Phe to its amide oxygen can give F a YGG-1, known as the a-radical with the spin density delocalized among the N-terminal NH 2 , the a-carbon of Phe and the N-terminal amide group.…”
Section: Theoretical Geometries and Irmpd Study Of [Fygg] +mentioning
confidence: 99%
“…Consequently, the β‐radical–driven, rather than the charge‐driven, pathway occurred selectively upon the CID of the [RG i –2 FG 7– i ] •+ species. A DFT analysis of small peptide models suggested that the unpaired electron of the C‐terminal [x m ] • fragment yielded from the β‐radical–induced C α –C bond cleavage is located in a π*(CO)‐like orbital, which can be destabilized by a proton on the peptide backbone. This theoretical prediction is consistent with experimental observations of the [a n ] + ions (from C α –C bond cleavage), instead of the [c n + 2H] + ions (from N–C α bond cleavage) being produced from the CID of [RG i –2 FG 7– i ] •+ species.…”
Section: Radical–induced Fragmentation Of Peptide Radical Cationsmentioning
confidence: 99%